2020
DOI: 10.1128/mbio.02090-20
|View full text |Cite
|
Sign up to set email alerts
|

H1 Hemagglutinin Priming Provides Long-Lasting Heterosubtypic Immunity against H5N1 Challenge in the Mouse Model

Abstract: Influenza virus infections leave a signature of immune memory that influences future responses to infections with antigenically related strains. It has been hypothesized that the first exposure in life to H1N1 influenza virus imprints the host immune system, potentially resulting in protection from severe infection with H5N1 later in life through hemagglutinin (HA) stalk-specific antibodies. To study the specific role of the HA on protection against infection without interference of cellular immunity or humora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…The major antigens HA and NA evolve more slowly within the influenza B lineages than within influenza A subtypes (Bedford et al, 2014, 2015; Vijaykrishna et al, 2015), and the amino acid sequence divergences are much lower between B/Victoria and B/Yamagata (≈ 14%, 2% and 7% in 2019 for the HA head, the HA stalk, and NA, respectively) than between H1N1 and H3N2 (≈ 66%, 50% and 60%, respectively) (Figure S23). Still, epitopes conserved within the lineages but variable between them (or between the lineages and their ancestor) might be the basis for imprinting protection against B/Yamagata (and potentially B/Victoria), as has been hypothesized for influenza A subtypes (Gostic et al, 2019; Arevalo et al, 2020a,b; Carreño et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The major antigens HA and NA evolve more slowly within the influenza B lineages than within influenza A subtypes (Bedford et al, 2014, 2015; Vijaykrishna et al, 2015), and the amino acid sequence divergences are much lower between B/Victoria and B/Yamagata (≈ 14%, 2% and 7% in 2019 for the HA head, the HA stalk, and NA, respectively) than between H1N1 and H3N2 (≈ 66%, 50% and 60%, respectively) (Figure S23). Still, epitopes conserved within the lineages but variable between them (or between the lineages and their ancestor) might be the basis for imprinting protection against B/Yamagata (and potentially B/Victoria), as has been hypothesized for influenza A subtypes (Gostic et al, 2019; Arevalo et al, 2020a,b; Carreño et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear if people have increased protection against their first infecting influenza B lineage. One hypothesized mechanism for immune imprinting in influenza A is antibodies to conserved epitopes (Gostic et al, 2016, 2019; Arevalo et al, 2020a,b; Carreño et al, 2020). Since B/Victoria and B/Yamagata diverged from each other more recently (Rota et al, 1990; Chen and Holmes, 2008; Dudas et al, 2015) and evolve antigenically much more slowly than the influenza A subtypes (Bedford et al, 2014, 2015; Vijaykrishna et al, 2015), conserved epitopes within a lineage might also be conserved between lineages, leading to strong cross-lineage protection by antibodies targeting those epitopes, regardless of which lineage was encountered first.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is growing interest in antibody, B, and T cell responses that target conserved influenza epitopes, which can provide broader cross-subtype protection, and provide a potential basis for universal influenza vaccination [71,72]. The proliferation of serological techniques to measure antibodies to conserved epitopes has revealed that, contrary to the classical within-subtype paradigm, OAS can also shape the quality and specificity of broadly protective, cross-subtype immunity [25,73]. Similarly, the breadth of cross-protection from imprinting and other cohort effects is context-dependent and depends on which epitopes are the dominant immune targets and how conserved those epitopes are.…”
Section: Cross-protective Breadthmentioning
confidence: 99%
“…For example, epitopes that are conserved between influenza subtypes that have and have not previously circulated in humans are, by definition, the only recognizable immune targets present on novel, avian subtypes, such as H5N1 and H7N9. Imprinting protection against zoonotic H5N1 and H7N9 infections involves memory of these conserved epitopes and provides broad cross-subtype protection [25,37,73]. On the other hand, memory responses against familiar seasonal strains are more likely to target variable, immunodominant epitopes, and in this context imprinting acts narrowly within a subtype [38,39].…”
Section: Cross-protective Breadthmentioning
confidence: 99%
“…Previous work has reported that antibodies developed following H1N1 infection or vaccination can cross-react with HA proteins of H5N1 strains (e.g. [16][17][18][19][20]).…”
Section: Monovalent Influenza Infection In Mice Generates a Subtype S...mentioning
confidence: 99%